Teacher Education for Research-based Practice in Expanded Roles: Finland's experience - Westbury, Ian; Hansén, Sven-Erik; Kansanen, Pertti; Björkvist, Ole (Scandinavian Journal or Educational Research, 2005)
Preparing teachers for a research-based professionalism has been the central mission of teacher education in Finland since the mid-1970s. More recently, as a result of such national policy developments as school-based curriculum development and local decision-making, the conception of teachers' work and professionalism has expanded. Drawing on experience within the teacher education programmes at the University of Helsinki and Åbo Akademi University, this paper discusses some of the programmatic issues that these developments have raised in class-teacher, i.e. “elementary‷0i0k0i0n0d0x, teacher education programmes. We focus in particular firstly on the research thesis that is a part of every teacher education programme in Finland, and the hallmark of the research-based professional ideal; and, secondly on the emerging issues that derive from the need to incorporate the expanded understanding of the teacher's role within the curriculum of teacher education.
Keywords: Finlande; formation des enseignants; utilisation des recherches